Pengaruh Biaya Produksi Terhadap Harga Jual Pada Usaha Kecil Sovina Naudin Konveksi Di Pasar Aur Kuning Kota Bukittinggi - Azizah, Nur; Elvira, Rini (Fakultas Ekonomi dan Bisnis Islam, 2025)
The Muslim fashion industry in Indonesia is experiencing rapid growth along with rising consumer demand and the emergence of small businesses in the garment industry. However, pricing for small businesses is often hampered by a lack of information about the actual production cost structure. The purpose of this research is to determine the effect of production costs on selling prices at the small company Sovina Naudin Konveksi in Aur Kuning Market, Bukittinggi. The method used is an associative quantitative methodology, where primary data is obtained through interviews, observation, and documentation, while secondary data is obtained from the business's financial records. This research data consists of 35 data sets sourced from production cost and selling price bookkeeping for the period January 2022 to November 2024. The testing methods used include data normality, linearity and homogeneity tests, simple linear regression tests, t-tests, and adjusted R-Squared tests. The results indicate that production costs influence 22.9 percent of selling prices, while 77.1 percent is influenced by other unspecified factors. The implications of this research are the importance of implementing a structured and accurate cost recording system at Sovina Naudin Konveksi so that selling prices can be set rationally, avoiding the risk of loss and increasing competitiveness, as well as contributing to the literature on cost accounting and pricing strategies in the Muslim fashion sector of MSMEs in traditional markets.